2017
DOI: 10.1128/jcm.00957-17
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Reverse Transcription-PCR for Simultaneous Surveillance of Influenza A and B Viruses

Abstract: Influenza A and B viruses are the causative agents of annual influenza epidemics that can be severe, and influenza A viruses intermittently cause pandemics. Sequence information from influenza virus genomes is instrumental in determining mechanisms underpinning antigenic evolution and antiviral resistance. However, due to sequence diversity and the dynamics of influenza virus evolution, rapid and high-throughput sequencing of influenza viruses remains a challenge. We developed a single-reaction influenza A/B v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
(28 reference statements)
3
29
0
Order By: Relevance
“…Viral RNA extracted from MDCK supernatant was used to sequence the HA gene of all influenza isolates at the NIC laboratory using Sanger sequencing. At the WHOCC (Melbourne), a single‐reaction, multiplex RT‐PCR method that amplifies the HA, NA, and M genomic segments of seasonal influenza A and B viruses for next‐generation sequencing was used, as previously described . Nucleotide sequences from the coding regions of the HA genes of A(H3N2), A(H1N1)pdm09, and influenza B viruses were aligned using the Mafft multiple aligner V1.3.7 in the Geneious V10.0.9 software package (http://www.geneious.com).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral RNA extracted from MDCK supernatant was used to sequence the HA gene of all influenza isolates at the NIC laboratory using Sanger sequencing. At the WHOCC (Melbourne), a single‐reaction, multiplex RT‐PCR method that amplifies the HA, NA, and M genomic segments of seasonal influenza A and B viruses for next‐generation sequencing was used, as previously described . Nucleotide sequences from the coding regions of the HA genes of A(H3N2), A(H1N1)pdm09, and influenza B viruses were aligned using the Mafft multiple aligner V1.3.7 in the Geneious V10.0.9 software package (http://www.geneious.com).…”
Section: Methodsmentioning
confidence: 99%
“…The complete matrix gene was sequenced from representative influenza A viruses using previously described methods, to ascertain the presence of mutations (eg, Ser31Asn) associated with resistance to the adamantine class of inhibitors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Sanger sequencing [6], next generation sequencing [7] or pyrosequencing [8] we found that from 1 March to 30 June 2017, all 310 tested Australian A(H3N2) viruses encoded M2 N31 indicating adamantane-resistance (M2 N31 viruses). However, in July, August and September 2017, two of 201 (1.0%), 10 of 115 (8.7%) and three of 145 (2.1%) tested A(H3N2) virus isolates, respectively, encoded M2 S31 indicating adamantane-sensitivity (M2 S31 viruses).…”
Section: Analysis Of the Adamantane-resistance Situation In Australiamentioning
confidence: 99%
“…15,16 There are real-time multiplex qRT-PCR assays for typing and subtyping seasonal influenza viruses. Some can even detect influenza B virus and determine influenza B viral lineage, 17,18 but none of these assays allows simultaneous typing and subtyping/lineage differentiation of all 4 seasonal influenza viruses in a single qRT-PCR reaction. Further, ddRT-PCR does not require a standard curve for quantification and it is less susceptible to PCR inhibitors.…”
mentioning
confidence: 99%